CMV seropositivity and T‐cell senescence predict increased cardiovascular mortality in octogenarians: results from the Newcastle 85+ study. Issue 2 (22nd December 2015) - Spyridopoulos, Ioakim; Martin‐Ruiz, Carmen; Hilkens, Catharien; Yadegarfar, Mohammad E.; Isaacs, John; Jagger, Carol; Kirkwood, Tom; von Zglinicki, Thomas
Summary: Although chronic infection with cytomegalovirus (CMV) is known to drive T lymphocytes toward a senescent phenotype, it remains controversial whether and how CMV can cause coronary heart disease (CHD). To explore whether CMV seropositivity or T‐cell populations associated with immunosenescence were informative for adverse cardiovascular outcome in the very old, we prospectively analyzed peripheral blood samples from 751 octogenarians (38% males) from the Newcastle 85+ study for their power to predict survival during a 65‐month follow‐up (47.3% survival rate). CMV‐seropositive participants showed a higher prevalence of CHD (37.7% vs. 26.7%, P = 0.030) compared to CMV‐seronegative participants together with lower CD4/CD8 ratio (1.7 vs. 4.1, P < 0.0001) and higher frequencies of senescence‐like CD4 memory cells (41.1% vs. 4.5%, P < 0.001) and senescence‐like CD8 memory cells (TEMRA, 28.1% vs. 6.7%, P < 0.001). CMV seropositivity was also associated with increased six‐year cardiovascular mortality (HR 1.75 [1.09–2.82], P = 0.021) or death from myocardial infarction and stroke (HR 1.89 [107–3.36], P = 0.029). Gender‐adjusted multivariate Cox regression analysis revealed that low percentages of senescence‐like CD4 T cells (HR 0.48 [0.32–0.72], P < 0.001) and near‐senescent (CD27 negative) CD8 T cells (HR 0.60 [0.41–0.88], P = 0.029) reduced the risk of cardiovascular death. For senescence‐like CD4, but not near‐senescent CD8 T cells, these associations remained robust after additional adjustment for CMV status, comorbidities, and inflammation markers. We conclude that CMV seropositivity is linked to a higher incidence of CHD in octogenarians and that senescence in both the CD4 and CD8 T‐cell compartments is a predictor of overall cardiovascular mortality as well as death from myocardial infarction and stroke.